Gut microbiota perturbations and neurodevelopmental impacts in offspring rats concurrently exposure to inorganic arsenic and fluoride. (July 2020) - Qiu, Yulan; Chen, Xushen; Yan, Xiaoyan; Wang, Jie; Yu, Guan; Ma, Wenyan; Xiao, Bo; Quinones, Sarah; Tian, Xiaolin; Ren, Xuefeng
Abstract: Many "hot spot" geographic areas across the world with drinking water co-contaminated with inorganic arsenic (iAs) and fluoride (F - ), two of the most common natural contaminants in drinking water. Both iAs and F - are known neurotoxins and affect neurodevelopment of children. However, very few studies have investigated the neurodevelopmental effects of concurrent exposure to iAs and F -, which could potentially pose a greater risk than iAs or F - exposure alone. Further, perturbations of gut microbiota, which plays a regulatory role in neurodevelopment, resulting from iAs and F - exposure has been reported in numerous studies. There is lacking of information regarding to the relationship among concurrent iAs and F - exposure, microbiome disruption, and neurodevelopmental impacts. To fill these gaps, we treated offspring rats to iAs (50 mg/L NaAsO2 ) and F - (100 mg/L NaF), alone or combined from early life ( in utero and childhood) to puberty. We applied Morris water maze test to assess spatial learning and memory of these rats and generated gut microbiome profiles using 16S rRNA gene sequencing. We showed that concurrent iAs and F - exposure caused more prominent neurodevelopmental effects in rats than either iAs or F - exposure alone. Moreover, Unsupervised Principal Coordinates Analysis (PCoA) and Linear Discriminant Analysis Effect Size (LEfSe) analysis of gut microbiome sequencing results separated concurrent exposure group from others, indicating a more sophisticated change of gut microbial communities occurred under the concurrent exposure condition. Further, a correlation analysis between indices of the water maze test and microbial composition at the genus level identified featured genera that were clearly associated with neurobehavioral performance of rats. 75% (9 out of 12) genera, which had a remarkable difference in relative abundance between the control and combined iAs and F - exposure groups, showed significantly strong correlations ( r  = 0.70–0.90) with the water maze performance indicators. Collectively, these results suggest that concurrent iAs and F - exposure led to more prominent effects on neurodevelopment and gut microbiome composition structures in rats, and the strong correlation between them indicates a high potential for the development of novel microbiome-based biomarkers of iAs and/or F - associated neurodevelopmental deficits.